Percepciones de la población costarricense e implicaciones de la pandemia COVID-19 en diferentes aspectos socioeconómicos y ambientales: informe de encuesta - Díaz-González, José Andrés (2021)
The survey Perceptions of the Costa Rican population and implications of the COVID-19 pandemic in different socioeconomic and environmental aspects, was applied between November 23 and 28, 2020; with the aim of studying the perceptions of the Costa Rican population about the implications generated by the pandemic caused by COVID-19 at the time of data collection. From the thematic point of view, this survey sought to cover a series of relevant topics to understand the various implications in different socioeconomic and environmental aspects, such as: perception of the notion of crisis in the country, working conditions, security and food sovereignty , domestic and care work, social protest in times of pandemic, waste management, environment and use of basic services. The questionnaire used for this study consisted of 38 questions, associated with the thematic variables of interest; as well as some sociodemographic variables such as sex, age, level of education, among others, which allow describing the characteristics of the surveyed population.